2013
DOI: 10.1111/asj.12134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of multiple candidate genes (LEP, LEPR, MC4R, PIK3C3, and VRTN) on production traits in Duroc pigs

Abstract: We evaluated multiple effects of genetic variations of five candidate loci (LEP, LEPR, MC4R, PIK3C3 and VRTN) on four production traits (average daily weight gain (ADG); backfat thickness (BFT); loin eye muscle area (EMA); and intramuscular fat content (IMF)) in a closed nucleus herd of pure Duroc pigs. Polymorphisms in LEPR, MC4R and PIK3C3 had significant single gene effects on ADG and BFT. The additive genetic variance in ADG and BFT (16.99% and 22.51%, respectively) was explained by genetic effects of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In a subsequent analysis, Hirose et al . () reported no significant association between the VRTN gene and IMF in the same Duroc population. The biological explanation for the result obtained by Hirose et al .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In a subsequent analysis, Hirose et al . () reported no significant association between the VRTN gene and IMF in the same Duroc population. The biological explanation for the result obtained by Hirose et al .…”
Section: Resultsmentioning
confidence: 88%
“…However, a subsequent report by Hirose et al . () indicated that there was no significant association between VRTN gene polymorphisms and IMF in the same population. Therefore, further study is required to evaluate the effect of VRTN gene polymorphisms on production traits and other economically important traits related to the number of vertebrae in different pig populations.…”
Section: Introductionmentioning
confidence: 91%
“…This may be due to different combinations of genes and their effects. The analysis of multiple genes (LEP, LEPR, MC4R, PIK3C3 and VRTN) effects on production traits in Duroc pigs showed independently influence on growth rate and fat deposition (Hirose et al, 2014). We studied the combined effect of the MC4R and GH genes.…”
Section: Discussionmentioning
confidence: 99%
“…In the association analysis performed by Houston et al (2004), the MC4R gene was significantly associated with mean daily gain, daily feed intake and backfat thickness. Hirose et al (2014), by evaluating the effects of candidate genes on production traits in Duroc pigs, detected positive correlations between the mean daily weight gain and backfat thickness of SNPs in the LEPR (c.2002T), MC4R (c.1426G) and PIK3C3 (c.2604C) genes.…”
Section: Mc4r (Snpg1578c>t)mentioning
confidence: 99%